Perbandingan Penggunaan Blush On Liquid dan Powder Terhadap Hasil Rias Wajah Panggung Pada Kulit Berminya - Putri, Fani Yonita; Sari, Dinda Erinta; Dewi, Siska Miga (Universitas Negeri Jakarta, 2023)
Blush on has a function to give blush to the cheeks. The proper use of blush on affects the makeup results. The research aims to analyze the differences in makeup results using liquid blush and powder blush on oily skin. It was a pre-experimental research with one shot case study. The population was female students majoring in cosmetology and beauty aged 19-25 years. The sample was 2 female students who had oily skin types selected using purposive sampling. Data collection techniques using observations, documentation and questionnaires. After the data obtained, normality and homogeneity test were carried out, and a hypothesis test using T test. The results showed that there was a difference in the subtleties of the use of blush liquid and powder on makeup of oily skin. This was evidenced by the analysis of the value of p = 0.003 (p < 0.05). In the flatness indicator, a p value = 0.029 (p < 0.05) is obtained, meaning that there was a difference in the flatness of the use of blush liquid and powder to the makeup on oily skin. In the resistance indicator, a value of p = 0.014 (p < 0.05) is obtained, meaning that there was a difference in the resistance of the use of blush liquid and powder to the makeup on oily skin.